K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 10 2021

a) ĐK : \(x\ge0\)

A = \(\frac{1}{\sqrt{x}+1}-\frac{3}{x\sqrt{x}+1}+\frac{1}{x-\sqrt{x}+1}\)

\(=\frac{x-\sqrt{x}+1-3+2\left(\sqrt{x}+1\right)}{\left(\sqrt{x}+1\right)\left(x-\sqrt{x}+1\right)}=\frac{\sqrt{x}\left(\sqrt{x}+1\right)}{\cdot\left(\sqrt{x}+1\right)\left(x-\sqrt{x}+1\right)}=\frac{\sqrt{x}}{x-\sqrt{x}+1}\)

b) \(A=\frac{\sqrt{x}}{x-\sqrt{x}+1}=\frac{x-\sqrt{x}+1-x+2\sqrt{x}-1}{x-\sqrt{x}+1}=1-\frac{\left(\sqrt{x}-1\right)^2}{x-\sqrt{x}+1}\le1\)

=> Max A = 1

Dấu "=" xảy ra <=> \(\sqrt{x}-1=0\)<=> x = 1

Vậy Max A = 1 <=> x = 1

27 tháng 10 2021

x = 1 nha

13 tháng 9 2016

a/ Ta có

P = \(\frac{1+\sqrt{x}}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}\) - \(\frac{2+x}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}\) - \(\frac{1+\sqrt{x}}{x+\sqrt{x}+1}\)

\(\frac{-\sqrt{x}}{1+\sqrt{x}+x}\)

14 tháng 9 2016

mình muốn hỏi câu b cơ bạn ơi